(untitled) (Scientia Agropecuaria, 2025)
The study investigates the phytochemical profiles of selected wild local vegetables in Central Kalimantan, Indonesia, assessing their potential health benefits in addressing nutritional deficiencies prevalent in the region. A comprehensive analysis was conducted on key metabolites, including phenols, flavonoids, carotenoids, alkaloids, phytosterol, terpenoid, saponin, and glucosinolates. The vegetables examined in this study included Solanum torvum, Cnesmone javanica, Gymnopetalum cochinense, Stenochlaena palustris, Helminthostachys zeylanica, Nauclea orientalis, Neptunia oleraceae, Crinum sp., Etlingera elatior, Calamus sp., Solanum ferox, Colocasia esculenta, Diplazium esculentum, and Rorippa indica. Using the Folin-Ciocalteu method, the total phenolic content in the ethanolic extract ranged from 107.20 to 7393.10 mg GAE 100 g-1. Total flavonoids varied from 27.17-1163.82 mg QE 100 g-1 fresh weight. Carotenoids, alkaloids, phytosterols, terpenoid, saponin ranging from 1.273-1448.80 mg 100 g-1, 78.94-1061.67 mg 100 g-1, 168.33 - 4926.67 mg 100 g-1, 914.44-15503.33 mg 100 g-1, respectively. Additionally, saponins and glucosinolates were found in concentrations ranging from 1742.22 to 19164.44 mg 100 g-1, and 92.4 to 4726.52 mg 100 g-1, respectively. N. orientalis, N. oleracea, and R. indica showed strong potential as functional foods due to their high levels of antioxidants and anti-inflammatory compounds. R. indica and D. esculentum stand out for their rich carotenoid. Additionally, the substantial amounts of phytosterols, saponins, glucosinolates, and terpenoids in N. oleracea, H. zeylanica, R. indica, and D. esculentum. Linking phytochemicals to health supports targeted diets for vulnerable groups, strengthened through diverse local vegetables and culturally adapted functional food products.